Migraine-tic syndrome: Two further case reports. (March 2017) - Hinze, Stephan; Davies, Paul; Astbury, Tess; Lane, Russell
Background: Migraine-tic syndrome was first reported in 2004 in a 44-year-old woman who had concomitant symptoms of both typical trigeminal neuralgia and migraine. We report here two further cases of migraine-tic syndrome and speculate on the relevance of this condition to the pathophysiology of headache. Case reports: A 43-year-old woman presented with typical trigeminal neuralgia symptoms that preceded the onset of migraine headache; both headache types responded to treatment with sumatriptan. A 35-year-old woman presented with trigeminal neuralgia that consistently followed the onset of migraine headache. The former aspect responded to baclofen, but the migraine headache required treatment with amitriptyline. Discussion: These two patients provide further support for the presence of an overlap syndrome of migraine-tic. We suggest that there is a common pathway for trigeminal neuralgia and migraine.